Understanding of Teachers Related to the Application of Character Values in Children of Kindergarten Age - Bustan, Radhiya; Mailani, Liana; Mukti, Yuliana (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2019)
The purpose of this research is to illustrate understanding of teachers related to the application of character values in kindergarten children. Respondents in this study were 35 Kindergarten teachers in Kelapa Gading, these teachers as questionnaire data collection respondents, then conducted in-depth interviews and observations on 3 Kindergarten in Kelapa Gading. The approach used qualitative method, and is strengthened by a quantitative approach in the form of a questionnaire with open-ended questions to determine the extent of the kindergarten teachers understanding of character values.Based on field research data sourced from open-ended questionnaires, interviews and field observations of teachers in AR, AD and AH kindergarten, it was found that most kindergarten teachers had understood the concept of character education in kindergarten children consisting of 18 character value. However, in applying it there are obstacles in the application of character education in general in AR, AH, and AD Kindergarten, namely the lack of intensive communication with parents and lack of school infrastructure in developing various media that is suitable for the development of kindergarten children